2017
DOI: 10.4081/oncol.2017.340
|View full text |Cite
|
Sign up to set email alerts
|

Developing a comprehensive Cardio-Oncology Program at a Cancer Institute: the Moffitt Cancer Center experience

Abstract: Cardio-oncology is a multidisciplinary field focusing on the management and prevention of cardiovascular complications in cancer patients and survivors. While the initial focus of this specialty was on heart failure associated with anthracycline use, novel anticancer agents are increasingly utilized and are associated with many other cardiotoxicities including hypertension, arrhythmias and vascular disease. Since its inception, the field has developed at a rapid pace with the establishment of programs at many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 59 publications
2
38
0
Order By: Relevance
“…Although HaH programs require lead time for start‐up and working through policy and payment issues, many organizations have access to or can build the services they need. This is similar to developing service lines in other areas . Recent reports in the media and through personal contact with the HaH‐Plus team demonstrate that health systems are increasingly implementing HaH programs and entering into risk contracts with insurers.…”
Section: Discussionmentioning
confidence: 74%
“…Although HaH programs require lead time for start‐up and working through policy and payment issues, many organizations have access to or can build the services they need. This is similar to developing service lines in other areas . Recent reports in the media and through personal contact with the HaH‐Plus team demonstrate that health systems are increasingly implementing HaH programs and entering into risk contracts with insurers.…”
Section: Discussionmentioning
confidence: 74%
“…This results in limited data to guide oncologists when they treat comorbid patients in the real-world and contributes to variations in management whereby physicians based their decisions on anecdotal experience. It is likely in these scenarios that physicians resort to the use of patient-related factors such as age and performance status, as well as the expertise of cardio-oncologists in formulating their treatment plans (32,33). Broadening of eligibility criteria in clinical trials to represent patients with a history of cardiovascular disease will increase the generalizability of results to real-world patients and optimize evidence-based treatment in this subpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted by the American College of Cardiology (ACC) distributed to centers with cardiology programs found that only 27% of centers had dedicated cardio-oncology programs. 24 An observational study of a multidisciplinary clinic demonstrated that despite 55% of patients experiencing a decrease of EF by at least 10%, 81% of the patients were able to complete greater than 90% of trastuzumab therapy. 25 A similar study of a larger patient population found that 191 of the 225 patients (85.3%) were able to complete their prescribed cancer treatments.…”
Section: Discussionmentioning
confidence: 99%